Post-streptococcal opsoclonus-myoclonus syndrome associated with anti-neuroleukin antibodies. Issue 4 (16th March 2006) - Candler, P M; Dale, R C; Griffin, S; Church, A J; Wait, R; Chapman, M D; Keir, G; Giovannoni, G; Rees, J H
Abstract : Background: Adult opsoclonus-myoclonus (OM), a disorder of eye movements accompanied by myoclonus affecting the trunk, limbs, or head, is commonly associated with an underlying malignancy or precipitated by viral infection. Methods: We present the first two reports of post-streptococcal OM associated with antibodies against a 56 kDa protein. Two young girls presented with opsoclonus and myoclonus following a febrile illness and pharyngitis. Protein purification techniques were employed. Amino acid sequences of human neuroleukin (NLK) and streptococcal proteins were compared using the protein-protein BLAST application. Results: The antigen was identified as NLK (glucose-6-phosphate isomerase, GPI). GPI is present on the cell surface of streptococcus making the protein a candidate target for molecular mimicry. Conclusions: We have identified NLK as an antigenic target in two patients with post-streptococcal OM. The pathogenicity of the antibodies is uncertain. The potential role of anti-neuroleukin antibodies in the pathogenesis of OM is discussed. We propose that OM may represent a further syndrome in the growing spectrum of post-streptococcal neurological disorders. The role of streptococcus in OM and the frequency with which anti-NLK responses occur in both post-infectious and paraneoplastic OM should be investigated further.